1993
DOI: 10.1093/nar/21.12.2953
|View full text |Cite
|
Sign up to set email alerts
|

General method for amplifying regions of very high G + C content

Abstract: The thermal cycler can be used with maximal efficiency by multiple individuals with different experiments when all PCR amplifications are optimized for one cycling program. More than 150 regions of genomic DNA from human and other species were successfully amplified in our laboratory by using one basic protocol that includes Taq DNA polymerase, primers containing 14 to 17 bp of genomic sequence, and standard cycling conditions of one minute at 94°C, two minutes at 500C, and three minutes at 720C. Application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 7 publications
0
41
0
Order By: Relevance
“…Previously, utilization of cosolvents, formamide (2) or glycerol (3) in the PCR was reported to significantly enhance specificity of the amplification. Most recently, a general method using native but not recombinant Pfu DNA polymerase was recommended to amplify regions of very high GC content (4). In the present study, we show that template denaturation with NaOH was required for PCR amplification of a highly GC-rich template.…”
mentioning
confidence: 58%
“…Previously, utilization of cosolvents, formamide (2) or glycerol (3) in the PCR was reported to significantly enhance specificity of the amplification. Most recently, a general method using native but not recombinant Pfu DNA polymerase was recommended to amplify regions of very high GC content (4). In the present study, we show that template denaturation with NaOH was required for PCR amplification of a highly GC-rich template.…”
mentioning
confidence: 58%
“…These conflicting results may be caused by the biases of both PCR methods and culture-based methods. The guanineplus-cytosine (G + C) content of template DNA has been reported to influence gene amplification by PCR [7,23]. Reysenbach et al (23) found that low G + C rDNA was preferentially amplified from a mixture of low and high G + C rDNA.…”
Section: MD Shawkey Et Al: Microbial Diversity Of Bird Feathersmentioning
confidence: 99%
“…The next 30 cycles were carried out with an annealing temperature of 658C instead of 438C. This method was based on a protocol described previously for PCR ampli®cation of very high GC rich sequences (Dutton et al, 1993).…”
Section: Construction Of C-jun 5' Utr Mutantsmentioning
confidence: 99%